Jenis dan Peranan Parasitoid dalam Mengendalikan Populasi Lalat Buah (Bactrocera dorsalis Complex.) (Diptera: Tephritidae) yang Menyerang Buah Mangga (Mangifera indica L) di Kabupaten Buleleng - SUSILA, I WAYAN; SUPARTHA, I WAYAN (Agrotrop : Journal on Agriculture Science, 2020)
The Role of parasitoid in controlling the population of fruit flies ( Bactrocera dorsalis Complex.) (Diptera: Tephritidae) who attacked mangoes ( Mangifera indica L) in Buleleng Regency. Thisresearch was conducted with the aim of knowing the role of parasitoids in controlling the population of fruit flies ( Bactrocera dorsalis Complex.) (Diptera: Tephritidae) on mango plants ( Mangifera indica L.) in Buleleng Regency. Field research was carried out at the Buleleng mango plantations while laboratory research was carried out at the Integrated Pest Management and Plant Disease Laboratory from April to July 2019.Field research was carried out at  the Buleleng mango plantations while laboratory research was carried out at the Integrated Pest Management laboratory and  was  carried out  from  April  to  July 2019.  Determination of the location of sampling  is  done  diagonally  and  fruits  infested  larvae  was  taken  purposively. The results showed that there were three species of fruit flies that attacked mango in Buleleng Regency, namely B. carambolae , B. papayae and B. occipitalis with an abundance of B. carambolae 39.3%, B. papayae 64.4% and B. occipitalis 0.3% and found three types of parasitoids namely Fopius sp , Diachasmimorpha sp . and Opius sp . The role of parasitoids in controlling fruit flies is still low when viewed from the parasitization rate of the three parasitoids namely Fopius sp. (2,24%), Diachasmimorpha sp. (1,9%), and Opius sp. (0,46%).